The degree of internationalisation and financial performance of South African multi-national enterprises - Singh, Sandhir (My University, 2013)
The world is far more interconnected economically, and with the removal of investment barriers, many firms are expanding their scope of operations beyond the borders of their home country through a process of internationalisation. This is a phenomenon that South African firms have embraced enthusiastically since the late 1990’s. A great deal of attention has been directed toward studying the relationship between the financial performance of firms and their degree of internationalisation, but the closest research on South African companies has primarily focussed on politico-economic issues rather than the internationalisation-performance relationship. This study, to the best of the author‘s knowledge, is one of the first to examine this relationship for South African multinationals. The study comprises a sample of eighty four JSE listed firms whose international operations are material enough to have been reported. Data on financial performance and foreign sales were collected from the published annual reports of these firms for the period from 2007 to 2012 and analysed in this study. Three hypotheses were proposed, corresponding to a linear, a quadratic, and a cubic relationship respectively, the results providing support only for the cubic relationship. Thus, the study indicates that the internationalisation-performance relationship is a sinus curve, where performance increases with internationalisation up to a first threshold, beyond which performance drops rapidly until a second threshold is reached, at which point performance begins to increase rapidly again. The results of this research reveal that performance does not increase monotonically with the degree of internationalisation adopted by the firm. There is instead, a “gulf of globalism” that South African firms must learn to come to terms with. Furthermore, the research reveals more questions than it answers. Consequently, there is a need for more extensive research in this area of study.
MBA thesis
Keywords: Multi-national corporations; Globalisation; Internationalisation; Financial performance